KAJIAN ASPEK LINGKUNGAN ALTERNATIF LOKASI UNTUK REPLACEMENT PABRIK III-B PT. PUSRI - IDAA Warmadewanthi (Purifikasi, 2021)
As a pioneer of urea fertilizer producer in Indonesia, PT. PUSRI is committed to realizing a sustainable fertilizer industry. Currently, PT. PUSRI has several problems which are 25% higher natural gas consumption due to the over 43 years old factory, increased investment and operational costs for old factory equipment, and spare parts that are expensive and difficult to source. For more efficient operation, PT. PUSRI plans to replace the plant and proposing 3 alternative locations, they are IA and IB on the East and West Sides of the Tanjung Api-Api area, and location II that is located in the PT. PUSRI area. To determine the most prospective location, each location needs environmental assessment. This study is using the SWOT analysis which will then be scored to show quantitative results. The results of the Strength analysis show that location II has a better score since it has a buffer zone as well as flora and fauna conservation. In the Weakness analysis, the IA and IB locations have shortcomings such as the inadequate raw water treatment technology. Location II has a disadvantage because it does not have domestic and industrial wastewater treatment technology. The results of the Opportunity analysis for IA and IB locations are considered to have more opportunities compared to location II. For Threat analysis, locations IA and IB are considered to have more challenges. One of which is the water body capacity to accept waste loads.